Neutrophils Facilitate Prolonged Inflammasome Response in the DAMP-Rich Inflammatory Milieu - Son, Seunghwan; Yoon, Sung-Hyun; Chae, Byeong Jun; Hwang, Inhwa; Shim, Do-Wan; Choe, Young Ho; Hyun, Young-Min; Yu, Je-Wook (Frontiers in Immunology, 2021)
Aberrant inflammasome activation contributes to various chronic inflammatory diseases; however, pyroptosis of inflammasome-active cells promptly terminates local inflammasome response. Molecular mechanisms underlying prolonged inflammasome signaling thus require further elucidation. Here, we report that neutrophil-specific resistance to pyroptosis and NLRP3 desensitization can facilitate sustained inflammasome response and interleukin-1β secretion. Unlike macrophages, inflammasome-activated neutrophils did not undergo pyroptosis, indicated by using in vitro cell-based assay and in vivo mouse model. Intriguingly, danger-associated molecular patterns (DAMP)-rich milieu in the inflammatory region significantly abrogated NLRP3-activating potential of macrophages, but not of neutrophils. This macrophage-specific NLRP3 desensitization was associated with DAMP-induced mitochondrial depolarization that was not observed in neutrophils due to a lack of SARM expression. Indeed, valinomycin-induced compulsory mitochondrial depolarization in neutrophils restored inflammasome-dependent cell death and ATP-induced NLRP3 desensitization in neutrophils. Alongside prolonged inflammasome-activating potential, neutrophils predominantly secreted interleukin-1β rather than other proinflammatory cytokines upon NLRP3 stimulation. Furthermore, inflammasome-activated neutrophils did not trigger efferocytosis-mediated M2 macrophage polarization essential for the initiation of inflammation resolution. Taken together, our results indicate that neutrophils can prolong inflammasome response via mitochondria-dependent resistance to NLRP3 desensitization and function as major interleukin-1β-secreting cells in DAMP-rich inflammatory region.